Extracellular activity of a bacterial protease associated with reduced phage infectivity - Ehud Herbst; Gael Rosen Blechman; Taya Fedorenko; Sarah Melamed; Gil Amitai; Rotem Sorek (PLoS ONE, 2026)
To defend against bacteriophage (phage) infection, bacteria have developed various defense systems, dozens of which were discovered and mechanistically studied recently. To date, almost all defense systems whose mechanisms were deciphered were shown to operate within the bacterial cell. Here we describe a secreted protease from the Actinobacterium Salinispora mooreana which, when expressed heterologously in Streptomyces coelicolor , reduces titers of two taxonomically related Siphoviridae phages. Antiphage effects were maintained when concentrated supernatant from S. coelicolor expressing the Salinispora protease was added externally to phage-containing medium, in either the presence or absence of bacterial cells, supporting an extracellular mechanism. We further show that phages can escape the antiphage effect of the Salinispora protease by mutating a tail-associated protein. The antiphage effect is associated with an increased proportion of phage particles devoid of DNA. Our data suggest antiphage activity of a secreted bacterial protease.